Development of a Heyzine E-Module Integrating Cassava Fermentation Ethnoscience for Acid-Base Chemistry - Kharisma Eka Yulianti Eka; Bayu Saputra; Gamilla Nuri Utami (Indonesian Journal of Chemistry and Environment, 2026)
Understanding acid-base concepts remains challenging for many students because these concepts are abstract and often disconnected from everyday experiences. This study aimed to develop and evaluate a Heyzine Flipbook-assisted e-module integrating cassava fermentation ethnoscience to support acid-base chemistry learning. The study employed a Research and Development (R&D) approach based on the Borg and Gall model. The developed e-module integrated interactive digital features, ethnoscience-based contexts, and multimedia elements to promote meaningful learning experiences. The product was validated by material and media experts, while its practicality and effectiveness were evaluated through teacher responses, student responses, and pretest-posttest assessments. The validation results indicated that the e-module was highly valid, with average scores of 92.51% from material experts and 91.88% from media experts. The practicality evaluation showed very positive responses from teachers (91.88%) and students (89.64%). Furthermore, students’ learning outcomes improved significantly, as reflected by the increase in the mean score from 41.39 on the pretest to 73.33 on the posttest. The normalized gain (N-gain) score was 0.54, indicating a moderate level of effectiveness in improving students’ understanding of acid-base concepts. These findings suggest that integrating ethnoscience and digital learning technology through a Heyzine Flipbook-assisted e-module provides an innovative, contextual, and effective learning resource for chemistry education.